Link of serum esterase enzymes with cognitive impairment in diabetic patients - Mahdavi P,; Mokhtari S,; Iranparvar M,; Amani F,; Mazani M,; Mostafalou S, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cognitive impairment is one of the main complications of diabetes and patients with cognitive impairment are considered to be in an intermediate stage of decreased cognition with higher risk of developing dementia and Alzheimer's disease. This study aimed at evaluating serum activity of two esterase enzymes including cholinesterase and paraoxonase 1 (PON 1) in diabetic patients and association with cognitive performance and metabolic parameters. In this crosssectional study, 128 diabetic patients were enrolled. Cognitive performance was evaluated using the Wechsler Adult Intelligence Scale-Revised (WAIS-R). Body mass index, fasting blood glucose, fasting blood insulin, insulin resistance, serum cholinesterase and paraoxonase 1 activity were measured. Prevalence of cognitive impairment was found to be 77% in the study population. Serum cholinesterase activity was found to be higher in diabetic patients with cognitive impairment than the patients with normal cognitive performance (p < 0.04). Further, a negative correlation was found between cognitive performance and cholinesterase activity, albeit statistically non-significant. Alteration in the activity of cholinesterase enzyme was shown to be associated with cognitive impairment in diabetic patients and future studies are required to find the pathophysiological mechanisms of diabetic cognitive dysfunction.